An Antimicrobial Treatment Assessment of Serratia marcescens Bacteremia and Endocarditis - Slain, Douglas; Howard, Catessa; Cooper, C. Garret (Frontiers in Antibiotics, 2022)
We assessed the treatment of Serratia marcescens bacteremia and endocarditis in one of the largest single center studies. We could not identify an advantage with any particular antibiotic treatment regimen in this study. Induction of AmpC or selection of ESBL organisms was not displayed by any of the organisms.